Breast reconstruction with breast implants - Grieco, Michele Pio; Simonacci, Francesco; Bertozzi, Nicolò; Grignaffini, Eugenio; Raposio, Edoardo (Acta Biomedica Atenei Parmensis, 2019)
Background: Breast cancer is the most common noncutaneous malignancy among women worldwide. After a breast cancer removal procedure, women are asked to decide about breast reconstruction, mainly to improve their life quality, and they can choose from among many options. Broadly, there are two different types of breast reconstruction procedures: prosthetic implant-based reconstruction and autologous tissue-based reconstruction. Methods: Implant-breast reconstruction is a minimally invasive procedure compared with autologous breast reconstruction. It is associated with fewer short- and long-term complications. Results: The ideal candidates for implant-based reconstruction are patients with non-redundant soft tissue coverage, who desire a moderate sized non-ptotic breast and have not been previously irradiated. Conclusion: The state of the art for implant-breast reconstruction is briefly described in this article.